2008
DOI: 10.1177/0960327108100001
|View full text |Cite
|
Sign up to set email alerts
|

Asthmatic symptoms after exposure to ethylenebisdithiocarbamates and other pesticides in the Europit field studies

Abstract: We conducted a multicenter prospective study to assess the effects of occupational exposure to ethylenebisdithiocarbamate fungicides and/or other pesticides on self-reported asthma and asthmatic symptoms. This multicenter study was conducted among 248 workers exposed to pesticides and 231 non-exposed workers from five field studies. The five field studies were carried out in The Netherlands, Italy, Finland, and two studies in Bulgaria. Subjects constituting this cohort completed a self-administered qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…No association was observed with the diagnosis of asthma (OR 1.19, 95% CI 0.93-1.52) or the occurrence of asthma attacks (OR 1.14, 95% CI 0.72-1.80) and urinary levels of ethylene thiourea, a metabolite of dithicarbamate fungicides [57].…”
Section: Wheeze and Asthmamentioning
confidence: 79%
“…No association was observed with the diagnosis of asthma (OR 1.19, 95% CI 0.93-1.52) or the occurrence of asthma attacks (OR 1.14, 95% CI 0.72-1.80) and urinary levels of ethylene thiourea, a metabolite of dithicarbamate fungicides [57].…”
Section: Wheeze and Asthmamentioning
confidence: 79%
“…Only one study in adults employed pesticide biomonitoring and this failed to find an association with asthma and ethylenebisdithiocarbamate exposed workers [16].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies relied on questionnaires to characterise likely exposures; an approach that can be vulnerable to recall bias and exposure misclassification. Relatively few studies employed biomonitoring to measure pesticide exposure [16,28,32] or biological effect monitoring [17]. A particular issue arose for those studies in agricultural settings where self-reports of pesticide exposure were used, but co-exposures to other agricultural respiratory hazards (e.g.…”
Section: Limitations Of Included Papersmentioning
confidence: 99%
“…Immunoglobulin, complement, mitogen-induced cytokyines, mitogen-induced proliferative response, and lymphocyte subtypes were used to investigate for alterations in functions of the immune system in these workers. The EUROPIT field study showed no association between exposure to EBCDs and an increased prevalence of allergic contact dermatitis, allergic rhinitis, asthma and asthmatic symptoms, or IgE-mediated allergic response to selected antigens in these workers Boers et al, 2008). An increase in T-cell proliferative response to mitogens (phytohemagglutinin, anti-CD3 monoclonal antibody and phorbol myristate acetate) was observed in workers manufacturing EBDC (mancozeb) compared to controls (Colosio et al, 1996).…”
Section: Human Health Effectsmentioning
confidence: 93%